Damage evolution of blended cement concrete under sodium sulfate attack in relation to ITZ volume content. (30th November 2018) - Wu, Kai; Kang, Wang; Xu, Linglin; Sun, Dandan; Wang, Fazhou; De Schutter, Geert
Highlights: ITZ quantity is determined through BSE image analysis and theoretical calculation. The damage is more severe for specimens with higher ITZ volume content. The use of slag is able to mitigate the adverse ITZ effect. Sulfur prefers to locate in the ITZ as a form of gypsum. Abstract: To understand the relation between the interfacial transition zone (ITZ) volume content and damage evolution of concrete under sodium sulfate attack, the development of length, mass and dynamic elastic modulus among specimens with varied aggregates was evaluated. After 12 months of exposure, there is a general trend toward increasing expansion, and reducing E Rd with increasing ITZ volume content for reference and limestone filler blended binary groups. No sign of degradation has been observed in slag blended specimens during the testing age. Element mapping exhibits that the sulfur presented as the form of gypsum tends to locate in the ITZ preferentially.